1998
DOI: 10.1212/wnl.50.4.1087
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum in attention-deficit hyperactivity disorder

Abstract: Clinical, neuroanatomic, neurobehavioral, and functional brain-imaging studies suggest a role for the cerebellum in cognitive functions, including attention. However, the cerebellum has not been systematically studied in attention-deficit hyperactivity disorder (ADHD). We quantified the cerebellar and vermal volumes, and the midsagittal areas of three vermal regions, from MRIs of 46 right-handed boys with ADHD and 47 matched healthy controls. Vermal volume was significantly less in the boys with ADHD. This red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(171 citation statements)
references
References 26 publications
7
155
2
7
Order By: Relevance
“…Additional support for the contention that MPH treats ADHD symptoms through the cerebellum was shown in a recent study by Anderson et al (2002) who demonstrated using fMRI that MPH decreases blood volume in the cerebellar vermis in ADHD children with greater symptoms of hyperactivity. Structural data also suggest that the cerebellar vermis may be implicated in ADHD with findings suggesting that the vermis is smaller in children with ADHD compared with healthy children (Berquin et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additional support for the contention that MPH treats ADHD symptoms through the cerebellum was shown in a recent study by Anderson et al (2002) who demonstrated using fMRI that MPH decreases blood volume in the cerebellar vermis in ADHD children with greater symptoms of hyperactivity. Structural data also suggest that the cerebellar vermis may be implicated in ADHD with findings suggesting that the vermis is smaller in children with ADHD compared with healthy children (Berquin et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Structural imaging studies in ADHD have repeatedly shown abnormalities in the cerebellum in children with ADHD (Berquin et al, 1998;Mostofsky et al, 1998). A recent fMRI study expanded knowledge of the relation between stimulants and the cerebellum (Anderson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional anatomical imaging studies of ADHD implicate decreased volume of the frontal lobes (Castellanos et al, 2002), parietal lobes (Sowell et al, 2003), basal ganglia (Castellanos and Giedd, 1994), REVIEW .. ............................................................................................................................................ corpus callosum , and cerebellum (Berquin et al, 1998). Imaging studies of brain physiology also support involvement of right frontal-basal ganglia circuitry, with a powerful modulatory influence from the cerebellum (see ) for a review).…”
Section: Mri Of Brain Anatomy In Atypical Pediatric Developmentmentioning
confidence: 99%
“…In structural imaging, the volumes of the whole brain, prefrontal cortex, left caudate nucleus, and cerebellum are all reduced [1][2][3][4][5][6][7][8] . Functional neuroimaging studies of patients with ADHD show the involvement of multiple neuronal systems in this disorder, including the prefrontal cortex, parietal cortex, striatum and cerebellum [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%